Three new species of Trachyphloeosoma Wollaston (Coleoptera: Curculionidae: Entiminae) from southeast Asia with the first record of the tribe Trachyphloeini from the Philippines - Borovec, Roman; Anderson, Robert (Zootaxa, 2022)
Three species of the genus Trachyphloeosoma Wollaston are described, illustrated and compared with related species: T. ales spec. n. from Taiwan, T. david spec. n. from China, Fujian province and T. philippinense spec. n. from the Philippines.